(untitled) (Sustainability in Debate, 2019)
In this article, we present some facts to contextualize the recent attacks against the Brazilian Amazon Monitoring Project carried out by the Brazilian government on the question of deforestation rates. We argue that these attacks represent a symptom of fundamental aspects of the case that need a sociological analysis of the ideologies that justify the reproduction of inequalities in the expansion of the frontier, as well as the influence that the beneficiaries of this process have acquired within the national policies for the Amazon region.